Edição de documentos mato-grossenses : características paleográficas - Campos, Angelita Heidmann (2012)
This master thesis aims to conduct a philological study of the “Record Book of the Royal Instructions to Governors of the Province of Mato Grosso” (Livro de Registro das Instruções Reais aos Governadores da Capitania de Mato Grosso), that consists of five manuscripts written between 1749 and 1788/1789. It belongs to the Public Record of Mato Grosso- Arquivo Público de Mato Grosso (APMT). From this five manuscripts fac-similar and semidiplomatic editions were made and elements and excerpts derived. Those ones were used to compose part of the History of the Eighteenth Century, the name index of the work, the paleographic and codicological descriptions, as well as samples of the ortographic aspects, of the metaplasms and of the stigmologic signs, especially the punctuation. As theoretical support, Spina (1977), Cambraia (2005), Andrade (2007) and others were used.